Associations of circulating ANGPTL3, C-terminal domain-containing ANGPTL4, and ANGPTL3/8 and ANGPTL4/8 complexes with LPL activity, diabetes, inflammation, and cardiovascular mortality - Silbernagel, Günther; Chen, Yan Q.; Li, Hongxia; Lemen, Deven; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Moissl-Blanke, Angela P.; Rudolf, Henrik; März, Winfried (Circulation, 2025)
BACKGROUND: - ANGPTL3/4/8 (angiopoietin-like proteins 3, 4, and 8) are important regulators of LPL (lipoprotein lipase). ANGPTL8 forms complexes with ANGPTL3 and ANGPTL4. ANGPTL4/8 complex formation converts ANGPTL4 from a furin substrate to a plasmin substrate, and both cleavages generate similar C-terminal domain-containing (CD)—ANGPTL4 fragments. Whereas several studies have investigated associations of free ANGPTL proteins with cardiovascular risk, there are no data describing associations of the complexes and CD-ANGPTL4 with outcomes or describing the effects of the complexes on LPL bound to GPIHBP1 (glycosylphosphatidylinositol HDL-binding protein 1). - METHODS: - Recombinant protein assays were used to study ANGPTL protein and complex effects on GPIHBP1-LPL activity. ANGPTL3/8, ANGPTL3, ANGPTL4/8, and CD-ANGPTL4 were measured with dedicated immunoassays in 2394 LURIC (Ludwigshafen Risk and Cardiovascular Health) study participants undergoing coronary angiography and 6188 getABI study (German Epidemiological Trial on Ankle Brachial Index) participants undergoing ankle brachial index measurement. There was a follow-up for cardiovascular death with a median (interquartile range) duration of 9.80 (8.75-10.40) years in the LURIC study and 7.06 (7.00-7.14) years in the getABI study. - RESULTS: - ANGPTL3/8 potently inhibited GPIHBP1-LPL activity and showed positive associations with LDL-C (low-density lipoprotein cholesterol) and triglycerides (both P<0.001). However, in neither study did ANGPTL3/8 correlate with cardiovascular death. Free ANGPTL3 was positively associated with cardiovascular death in the getABI study but not the LURIC study. ANGPTL4/8 and especially CD-ANGPTL4 were positively associated with the prevalence of diabetes, CRP (C-reactive protein; all P<0.001), and cardiovascular death in both studies. In the LURIC and getABI studies, respective hazard ratios for cardiovascular mortality comparing the third with the first ANGPTL4/8 tertile were 1.47 (1.15-1.88) and 1.68 (1.25-2.27) when adjusted for sex, age, body mass index, and diabetes. For CD-ANGPTL4, these hazard ratios were 2.44 (1.86-3.20) and 2.76 (2.00-3.82). - CONCLUSIONS: - ANGPTL3/8 potently inhibited GPIHBP1-LPL enzymatic activity, consistent with its positive association with serum lipids. However, ANGPTL3/8, LDL-C, and triglyceride levels were not associated with cardiovascular death in the LURIC and getABI cohorts. In contrast, concentrations of ANGPTL4/8 and particularly CD-ANGPTL4 were positively associated with inflammation, the prevalence of diabetes, and cardiovascular mortality.
Online veröffentlicht: 11. Oktober 2024
Gesehen am 04.08.2025